The Cleistogamous Breeding System: A Review of Its Frequency, Evolution, and Ecology in Angiosperms - Culley, Theresa M; Klooster, Matthew R (The Botanical review, 2007)
Cleistogamy, a breeding system in which permanently closed, self-pollinated flowers are produced, has received increasing attention in recent years, but the last comprehensive review of this system was over 20 years ago. The goal of this paper is to clarify the different types of cleistogamy, quantify the number of families, genera, and species in which cleistogamy occurs, and estimate the number of times and potential reasons why cleistogamy has evolved within angiosperms. Cleistogamous species were identified through a literature survey using 13 online databases with references dating back to 1914; only those species well-supported by floral descriptions or empirical data were included in the data set. On the basis of this survey, we suggest the use of three different categories of cleistogamy in future studies: dimorphic, complete, and induced. Based on these categories, cleistogamy in general is present in 693 angiosperm species, distributed over 228 genera and 50 families. When analyzed on a family level across the angiosperms, the breeding system has evolved approximately 34 to 41 times. Theoretical investigations indicate that the evolution of cleistogamy in taxa may be influenced by the presence of heterogeneous environments, inbreeding depression and geitonogamy, and differential seed dispersal, as well as by various ecological factors and plant size. Cleistogamy will undoubtedly be discovered in additional species as the reproductive biology of more taxa is examined in the future. Such information will be invaluable for understanding the selective pressures and factors favoring the evolution of cleistogamy as well as the evolutionary loss of this breeding system, a subject that has received little attention to date.